伺服驱动系统 (2017)
本发明提供种伺服驱动系统，能够提高伺服控制的控制响应性，根据控制装置的各轴的特性，将控制运算部分配到伺服放大器或伺服控制器。本发明的伺服驱动系统中，对每个轴控制伺服马达的伺服控制部具有生成伺服马达的指令的特性参数文件生成部、控制伺服马达的位置的位置控制部、控制伺服马达的速度的速度控制部、以及控制伺服马达的马达电流的电流控制部，特性参数文件生成部、位置控制部、速度控制部及电流控制部分别对每个轴分配于伺服放大器或伺服控制器。 The invention provides a servo driving system capable of improving the control response of the servo control, and according to the characteristics of each axis of the control device, assigning a control arithmetic unit to the sevo amplifier or servo controller. The servo driving system of the present invention, the servo control unit of each axis control servo motor comprises a file generating unit generating the characteristic parameter of the commands of the servo motor, a position control unit controlling the position of the servo motor, a speed control unit controlling the speed of the servo motor, and a current control unit controlling the current of the servo motor motor. The characteristic parameter file generating unit, the position control unit, speed control unit and the current control por